2019
DOI: 10.1186/s13578-019-0271-5
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 ameliorates experimental colitis involving regulation of autophagy of macrophages in mice

Abstract: BackgroundPreviously, we have demonstrated that IL-33 administration protecting TNBS-induced experimental colitis is associated with facilitation of Th2/Tregs responses in mice. However, whether IL-33 regulates autophagy to ameliorate experimental colitis is unclear.ResultsIL-33 administration (2 μg/day, intraperitoneal injection), while facilitating Th2/Tregs responses, also enhances the autophagy in mice with TNBS-induced colitis as well as macrophages. In the meantime, we observed that inhibition of the aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…[37]. In addition, IL-33, which was found to ameliorate experimental colitis in mice by inhibiting autophagy of macrophages [24], have a neuroprotective effect by inhibition on autophagy [22,23]. Similarly, our results also showed that IL-33/ST2 signaling pathway regulated the degranulation of mast cells through autophagy (Figures 2 and 5).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…[37]. In addition, IL-33, which was found to ameliorate experimental colitis in mice by inhibiting autophagy of macrophages [24], have a neuroprotective effect by inhibition on autophagy [22,23]. Similarly, our results also showed that IL-33/ST2 signaling pathway regulated the degranulation of mast cells through autophagy (Figures 2 and 5).…”
Section: Discussionsupporting
confidence: 74%
“…IL-33 is a recently discovered cytokine that is produced by specialized epithelial cells and plays important roles in the pathogenesis of various allergic diseases [19][20][21]. In addition, IL-33 is able to suppress autophagy and exerts neuroprotection functions [22,23] and ameliorates experimental colitis by promoting autophagy of macrophages [24]. It is, therefore, possible that epithelial cells regulate autophagy and degranulation of mast cells through IL-33, which could be a potential mechanism of the pathogenesis of AR.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that IL-33, thought to be ST2, induces B1 B cell activation, leading to a rapid proliferation and production of natural IgM (38). Besides inducing a Th2 immune response, the IL-33/ST2 axis has also been extensively demonstrated to participates in regulating immune homeostasis upon tissue injury (15,33,33,36,37,(63)(64)(65)(66)(67)(68)(69). In the context of pregnancy, Huang and co-authors have recently demonstrated that choriodecidual B1 B cells protect against inflammationinduced PTB by producing progesterone-induced blocking factor 1 (PIBF1) in response to the mucosal alarmin IL-33 (31).…”
Section: Discussionmentioning
confidence: 99%
“…Statins promote autophagy fusion with lysosomes to reduce bacterial burdens in macrophages [26,50]. IL-33 treatment enhances autophagy in mice with experimental colitis [51]. Intranasal administration of IL-33 was shown to promote IL-13-dependent autophagy and that this axis regulated mucus secretion by airway epithelial cells [52].…”
Section: Discussionmentioning
confidence: 99%